Python : zero to coder (Video collection). (LiveLessons (Boston, Massachusetts), 2022)
Overview 16+ Hours of Video Instruction Description This master class includes the following courses: Introduction to Python: Learn How to Program Today with Python Next Level Python Introduction to Python: Learn How to Program Today with Python This 7+ hour LiveLesson video helps absolute beginners get started in Python, which is one of the most popular and in-demand languages in use today. Python was created with beginners in mind, but don't let its simple nature fool you. It is used by professional developers in a wide range of applications, such as web programming, data analysis, machine learning, and DevOps. While most introductory courses focus on the basics of the language, this course goes one step further to explain how Python is used in practice in the fields of data analysis and web development. Students learn fundamental programming concepts, such as conditionals, loops, and functions. They are given hands-on, modular problems to solve so they can progress as they go. Finally, students tie it all together and experiment with some real programming in the form of text-based games. The overall goal of this course is to help absolute beginners learn from scratch, navigate the world of software development, and then kick-start their programming journey with introductions to two of the more common uses of Python: data analysis and web development. The companion files for this LiveLesson can be accessed from https://github.com/ariannedee/intro-to-python-livelessons. Next Level Python Python was originally designed with learners in mind. It is also used by professional developers in a wide range of applications. In this LiveLesson, you learn essential skills to move past a beginner level and become a proper Python developer. Such skills include using external libraries, managing project environments, handling exceptions, and making HTTP requests. By the end of the lessons, you will have created a web scraper in Python that gathers data from a website and outputs it into a CSV formatted file. Along the way, you will be introduced to key software construction concepts like testing, debugging, and refactoring. The source code repository for this LiveLesson is kept at https://github.com/ariannedee/next-level-python-livelessons. About the Instructor Arianne Dee is a freelance software developer and educator from the University of British Columbia and an instructor for Canada Learning Code and MakerLabs in Vancouver, BC. Arianne's Intro to Programming with Python LiveLessons (Addison Wesley) has received 5-star reviews. Arianne has a following in the Python community, with her well-thought-out live trainings and videos. About Pearson Video Training Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Sams, and Que. Topics include IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video.